Design of a compact device to generate and test beams with orbital angular momentum in the EUV: erratum - Pabon Riaño, Dudbil Olvasada (2019)
The paper by Pabon et al. in Applied Optics [1] was published nearly simultaneously with the article by Pabon et al. in Optica Pura y Aplicada (OPA) [2] by virtue of having been presented to the Ibero-American Meeting IX RIAO/XII OPTILAS. For this reason, the article published in Applied Optics, which contains numerical simulations, experiments in visible wavelengths, and the scaling to EUV wavelengths, did not include the citation to the article published in OPA, which contains the preliminary numerical simulations. However, given that paper [2] reports research carried out before that reported in Ref. [1], it should be considered as part of the references of [1].